LA PHILOSOPHIE EN DIALOGUE - Denis VERNANT (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
Philosophy in Dialogue. Today one of the modalities of the pedagogical practice in college and high school is the use of Discussions with Philosophical Aim. In the following we would simply like to specify what kind of philosophy can be practiced in such contexts and what it can bring to pupils and high school students in terms of methods and content.